Menakar Kesiapan Sekolah Dengan Kemunculan Perilaku Delinkuen Pada Siswa Sekolah Dasar - Yuli Fitria (Journal on Education, 2023)
Delinquent behavior or commonly known as naughty behavior in elementary school students can have a negative impact on the learning process at school and must be addressed immediately. It is suspected that one of the causes of delinquent behavior emergence in elementary school students is that children do not have mental readiness when entering school so it is necessary to be investigated. This study aimed to reveal the correlation between psychological mental readiness in early elementary school students and the emergence of delinquent behavior. The research approach used a quantitative, purposive sampling technique with a total of 102 students as participants. The measuring tools used were the school readiness scale and the delinquent behavior scale at a child’s age. Data analysis used simple regression analysis. The results showed that there was a significant negative correlation between school readiness and delinquent behavior (r = -0.509, p = 0.014). This means that the higher the psychological readiness of students to enter school, the lower the tendency to engage in delinquent behavior. The conclusions can be drawn based on the analysis results by developing children's mental readiness to increase self-readiness to enter the school level and minimize the emergence of delinquent behavior.